Born in a mighty bad land : the violent man in African American folklore and fiction - Bryant, Jerry H., 1928- (Blacks in the diaspora., 2003)
The figure of the violent man in the African American imagination has a long history. He can be found in 19th-century bad man ballads like 'Stagolee' and 'John Hardy, ' as well as in the black convict recitations that influenced 'gansta' rap. Born in a Mighty Bad Land connects this figure with similar characters in African American fiction.